The Semantic Web: ESWC 2012 Satellite Events - Simperl, E (Springer, 2015)
This book constitutes the thoroughly refereed post-proceedings of the satellite events of the 9th International Conference on the Semantic Web, ESWC 2012, held in Heraklion, Crete, Greece, in May 2012. This volume contains 49 full papers and 13 short papers describing the posters and demonstrations. (SUGGESTION/ HELP needed).